Making Cities Resilient to Climate Change : Identifying ‘Win-Win’ Interventions - Dulal, Hari Bansha (Taylor and Francis, 2016)
Urbanization is truly a global phenomenon. Starting at 39% in 1980, the urbanization level rose to 52% in 2011. Ongoing rapid urbanization has led to increase in urban greenhouse gas (GHG) emissions. Urban climate change risks have also increased with more low-income urban dwellers living in climate sensitive locations. Despite increased emissions, including GHGs and heightened climate change vulnerability, climate mitigation and adaptation actions are rare in the cities of developing countries, often viewed as “low-priority" issues, if anything. Cities are overwhelmed with worsening congestion, air pollution, crime, waste management, and unemployment problems. Lack of resources and capacity constraints are other factors that discourage cities from embarking on climate change mitigation and adaptation pathways. Given the multitude of problems faced, there is simply no appetite for stand-alone urban climate change mitigation and adaptation policies and programs. Urban mitigation and adaptation goals will have to be achieved as co-benefits of interventions targeted at solving pressing urban problems and challenges given the ground realities at the moment. The paper identifies administratively simple urban interventions that can help cities solve some of their pressing service delivery and urban environmental problems, while simultaneously mitigating rising urban GHG emissions and vulnerability to climate change. The paper also identifies implementation barriers and presents barrier removal options in order to facilitate wider diffusion of these interventions.